Structure of the cobalamin‐binding protein of a putative O‐demethylase from Desulfitobacterium hafniense DCB‐2. (30th July 2013) - Sjuts, Hanno; Dunstan, Mark S.; Fisher, Karl; Leys, David
<x xml:space="preserve">Abstract</x> This study describes the identification and the structural and spectroscopic analysis of a cobalamin‐binding protein (termed CobDH) implicated in O‐demethylation by the organohalide‐respiring bacterium Desulfitobacterium hafniense DCB‐2. The 1.5 Å resolution crystal structure of CobDH is presented in the cobalamin‐bound state and reveals that the protein is composed of an N‐terminal helix‐bundle domain and a C‐terminal Rossmann‐fold domain, with the cobalamin coordinated in the base‐off/His‐on conformation similar to other cobalamin‐binding domains that catalyse methyl‐transfer reactions. EPR spectroscopy of CobDH confirms cobalamin binding and reveals the presence of a cob(III)alamin superoxide, indicating binding of oxygen to the fully oxidized cofactor. These data provide the first structural insights into the methyltransferase reactions that occur during O‐demethylation by D. hafniense.